2009
DOI: 10.1128/aac.00051-09
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Gentamicin or Rifampin Does Not Enhance the Effectiveness of Daptomycin in Treatment of Experimental Endocarditis Due to Methicillin-Resistant Staphylococcus aureus

Abstract: [20%]; P ‫؍‬ 0.01 and P ‫؍‬ 0.02, respectively). No statistical difference was noted between daptomycin plus gentamicin and daptomycin alone for MRSA treatment. In the combination arm, all isolates from vegetations remained susceptible to daptomycin, gentamicin, and rifampin. Sixty-one percent of the isolates (8/13) acquired resistance to rifampin during monotherapy. In the daptomycin arm, resistance was detected in only one case, in which the daptomycin MIC rose to 2 g/ml among the recovered bacteria. In conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
3
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 31 publications
0
33
3
2
Order By: Relevance
“…However, in vivo studies have reported different results. Miró et al found that the addition of gentamicin or rifampin did not enhance the effectiveness of daptomycin in the treatment of experimental endocarditis due to MRSA (15). Furthermore, our study found a poor effect of daptomycin monotherapy, and even of daptomycin combined with rifampin, against MRSA in biofilm.…”
contrasting
confidence: 44%
“…However, in vivo studies have reported different results. Miró et al found that the addition of gentamicin or rifampin did not enhance the effectiveness of daptomycin in the treatment of experimental endocarditis due to MRSA (15). Furthermore, our study found a poor effect of daptomycin monotherapy, and even of daptomycin combined with rifampin, against MRSA in biofilm.…”
contrasting
confidence: 44%
“…There are conflicting results in experimental models [106,107] but recent clinical data in severe staphylococcal infections reported good results with this combination [108]. Interestingly, the authors found a good correlation between results of synergy using the chequerboard method and clinical outcome but not with killing curves.…”
Section: Combination Therapy With Daptomycinmentioning
confidence: 99%
“…Rifampicynę należy stosować tylko w przypadku zakażenia obcego materiału w sercu, tak jak w PVE po 3-5 dniach skutecznej antybiotykoterapii, kiedy mija bakteriemia. Uzasadnieniem takiego sposobu postępowania jest prawdopodobny antagonistyczny wpływ skojarzenia antybiotyków z rifampicyną wobec planktonowych/replikujących się bakterii [130], synergia widoczna wobec nieaktywnych bakterii i zapobieganie powstawaniu szczepów opornych na rifampicynę [131]. 3.…”
Section: Zasady Ogólneunclassified